Analisis Perbandingan Pertumbuhan Ekonomi, Konsumsi, Investasi dan Ekspor Neto di Sumatera Selatan Sebelum dan Sesudah Krisis Finansial Global Tahun 2008 - Gita Triana Putri; Novegya Ratih Primandari (Ekonomika, 2021)
This study discusses a comparative analysis of economic growth, consumption, investment and net exports in South Sumatra before and after the 2008 global financial crisis. Data collection techniques used were data on economic growth, consumption, investment and net exports obtained from the official website. The analytical method used is the Paired Simple T-Test. The calculation results show that: (a) conditions of economic growth, there were significant differences in economic growth in South Sumatra before and after the 2008 global financial crisis; (b) consumption conditions, there are significant differences in consumption in South Sumatra before and after the 2008 global financial crisis; (c) investment conditions, there were significant differences in investment in South Sumatra before and after the 2008 global financial crisis and (d) net export conditions there were significant differences in net exports in South Sumatra before and after the 2008 global financial crisis. Advice proposed that the South Sumatra government can pay more attention to the impact of the financial crisis on the economy, especially on export-import activities. Furthermore, the government can imply the implementation of policies to anticipate the impact of the global crisis both in South Sumatra and the need for an increase and optimization of economic potential both regional and central so that when the crisis occurs again.